Differential sensitivity to acute cholesterol lowering of activation mediated via the high-affinity IgE receptor and Thy-1 glycoprotein - Surviladze, Z; Dráberová, L; Kovárová, M; Boubelík, M; Dráber, P (European journal of immunology, 2001)
Lateral cross-linking of transmembrane high-affinity IgE receptors (FcepsilonRI) or glycosylphosphatidylinositol-anchored Thy-1 glycoproteins on the surface of rat mast cells and rat basophilic leukemia (RBL) cells triggers the signaling pathways that lead to the release of allergy mediators. Although both of these pathways are initiated by an increased activity of Lyn kinase, the exact mechanism by which Lyn kinase interacts with aggregated FcepsilonRI and Thy-1 is not completely understood. Here we demonstrate that pretreatment of RBL cells with methyl-beta-cyclodextrin (MBCD) resulted in a dose- and time-dependent decrease in cellular cholesterol, increased detergent solubilization of Thy-1 and Lyn kinase, and a transient increase in tyrosine phosphorylation of several proteins. Acute lowering of cholesterol suppressed the activation through Thy-1, as determined by tyrosine phosphorylation of Syk kinase and some other proteins, and modulation of free cytoplasmic calcium. In contrast, the FcepsilonRI-mediated activation events were more resistant. Thy-1 and FcepsilonRI in MBCD-pretreated cells also differed in the extent of aggregation after cross-linking: Thy-1 formed large caps, whereas FcepsilonRI accumulated in small patches. MBCD treatment induced an increased release of secretory components in both Thy-1- and FcepsilonRI-activated cells. The combined data indicate that cholesterol depletion does not merely block receptor signaling but has more complex consequences.
Keywords: src-Family Kinases; fosforylace; Cholesterol; myši; Protein-Tyrosine Kinases; tyrosinkinasy; Phosphorylation; Intracellular Signaling Peptides and Proteins; Rabbits; Animals; Mast Cells; mastocyty; Mice; Cyclodextrins; glykosfingolipidy; skupina kinas odvozených od src-genu; cholesterol; Thy-1 Antigens; Receptors, IgE; Glycosphingolipids; antigeny Thy-1; kinasa Syk; tyrosin; receptory IgE; zvířata; cyklodextriny; Syk Kinase; Tyrosine; intracelulární signální peptidy a proteiny; Enzyme Precursors; prekurzory enzymů; beta-Cyclodextrins; králíci; beta-cyklodextriny